smART Brain - Cheah, Pike See (Universiti Putra Malaysia Press, 2016)
In the smART Brain section, visitors can expect a dynamic yet entertaining science journey and educational time. “The Master Hat” is specially designed to portray the left-right brain dominance : the right brain is often regarded as the more creative side whilst the left brain is regarded as the analytical side.